Bright red emission with high color purity from Eu(iii) complexes with π-conjugated polycyclic aromatic ligands and their sensing applications. Issue 2 (4th January 2022) - Kitagawa, Yuichi; Tsurui, Makoto; Hasegawa, Yasuchika
Abstract : In this review, we summarize the research progress on π-conjugated Eu(iii ) luminophores exhibiting bright emission and their physical sensing applications. Abstract : Eu(iii ) complexes emit red light with a high color purity and have consequently attracted attention for development toward display and physical sensing applications. The characteristic pure color emission originates from the intra-4f–4f transition, and the brightness strongly depends on the electronic and steric structures of organic ligands. A large π-conjugated ligand design with a large absorption coefficient has been actively studied for achieving bright emission. The π-conjugated Eu(iii ) luminophores also provide oxygen and temperature sensing properties by controlling their excited state dynamics based on π-electron systems. A comprehensive understanding of the design strategy of large π-conjugated ligands is crucial for the further development of luminescent Eu(iii ) complexes. In this review, we summarize the research progress on π-conjugated Eu(iii ) luminophores exhibiting bright emission and their physical sensing applications.